Outcomes of Cannabis Use During Pregnancy Within the American Association of Birth Centers Perinatal Data Registry 2007-2020: Opportunities Within Midwifery-Led Care. Issue 3 (July 2022) - Joseph-Lemon, Lodz; Thompson, Heather; Verostick, Lori; Shizuka Oura, Haley; Jolles, Diana R
Abstract : Background: Healthcare providers require data on associations between perinatal cannabis use and birth outcomes. Methods: This observational secondary analysis come from the largest perinatal data registry in the United States related to the midwifery-led birth center model care (American Association of Birth Centers Perinatal Data Registry; N = 19 286). Births are planned across all birth settings (home, birth center, hospital); care is provided by midwives and physicians. Results: Population data show that both early and persistent self-reports of cannabis use were associated with higher rates of preterm birth, low-birth-weight, lower 1-minute Apgar score, gestational weight gain, and postpartum hemorrhage. Once controlled for medical and social risk factors using logistic regression, differences for childbearing people disappeared except that the persistent use group was less likely to experience "no intrapartum complications" (adjusted odds ratio [aOR] = 0.49; 95% confidence interval [CI], 0.32-0.76; P < .01), more likely to experience an indeterminate fetal heart rate in labor (aOR = 3.218; 95% CI, 2.23-4.65; P < .05), chorioamnionitis (aOR = 2.8; 95% CI, 1.58-5.0; P < .01), low-birth-weight (aOR = 1.8; 95% CI, 1.08-3.05; P < .01), and neonatal intensive care unit (NICU) admission (aOR = 2.4; 95% CI, 1.30-4.69; P < .05). Conclusions: Well-controlled data demonstrate that self-reports of persistent cannabis use through the third trimester are associated with an increased risk of low-birth-weight and NICU admission.